The Transfer of Imagos in Translation of Nationally Oriented and Transnational Texts (As Seen in the Novels of Czech, Slovak and Russian Writers) - Kniazkova, Viktoria S.; Kotova, Marina Yu. (Bohemistyka, 2021)
This work is an attempt to highlight the specific features of nationally oriented and transnational prose texts. Nationally oriented texts reflect history, culture and identity of one nation (e.g. prose by Solzhenitsyn and Krištúfek), transnational texts compound two or more national culture codes (e.g. prose by Brežná, Kaminer, Moníková and Škvorecký). The goal of this study is to identify specific difficulties in the process of their translation and transfer of imagos, that is stereotypical images of other identities. With the use of stylistic method, some typical ways of transmitting these imagos in literary texts are demonstrated.